Non-invasive Hemoglobin Measurement for Anemia Diagnosis - Raditya Artha Rochmanto; Hasballah Zakaria; Ratih Devi Alviana; Nurhalim Shahib (IAES Indonesia Section, 2017)
Hemoglobin is important part of red blood cell to transport oxygen and carbon dioxide. Hemoglobin concentration in the blood can be used as physical condition parameter. A low hemoglobin level is called anemia and high hemoglobin level is called polycythemia. WHO has determined the anemia cut off level of hemoglobin concentration based on age, sex, and condition (pregnant or not). Currently, accurate and reliable hemoglobin concentration measurement uses invasive methods such as cyanmethemoglobin and automated hematology analyzer. But these methods are expensive, not real time, high infection risk, and need special techniques. Non-invasive methods offer a better alternative because it has low infection risk, instant result, and portable in size. This work developed a non-invasive hemoglobin measurement for anemia diagnosis based on optical spectroscopy. The system utilized LED and photodiode as optical sensor placed on the fingertip. Photodiode just could obtain DC component, so the signal conditioning circuit which consisted of HPF, LPF and amplifier was used to obtain the AC component of the signal. This system used microcontroller to control the operation of the hardware and to calculate the hemoglobin concentration.Hemoglobin is important part of red blood cell to transport oxygen and carbon dioxide. Hemoglobin concentration in the blood can be used as physical condition parameter. A low hemoglobin level is called anemia and high hemoglobin level is called polycythemia. WHO has determined the anemia cut off level of hemoglobin concentration based on age, sex, and condition (pregnant or not). Currently, accurate and reliable hemoglobin concentration measurement uses invasive methods such as cyanmethemoglobin and automated hematology analyzer. But these methods are expensive, not real time, high infection risk, and need special techniques. Non-invasive methods offer a better alternative because it has low infection risk, instant result, and portable in size. This work developed a non-invasive hemoglobin measurement for anemia diagnosis based on optical spectroscopy. The system utilized LED and photodiode as optical sensor placed on the fingertip. Photodiode just could obtain DC component, so the signal conditioning circuit which consisted of HPF, LPF and amplifier was used to obtain the AC component of the signal. This system used microcontroller to control the operation of the hardware and to calculate the hemoglobin concentration.